Experimental and theoretical studies of photoluminescence in Zns obtained by microwave-assisted solvothermal method - Ferrer, Mateus M.; Santana, Yuri V. B. de; Raubach, Cristiane W.; Sambrano, Julio Ricardo[UNESP]; Longo, Elson [UNESP] (Bentham Science Publishers, 2013)
A shift of the photoluminescence (PL) emission was observed in ZnS prepared by microwave assisted solvothermal method with the increase of the time in microwave. In this work we reported a study of the optical behavior linking with the structural disorder according to XRD and FEG-TEM results. The reduction of intrinsic defects in the lattice is responsible for the decrease of electronic levels in the band gap changing the PL profile. This effect was confirmed by electronic structure calculations.
Keywords: Semiconductor; Zinc compounds; Optical properties; Density functional theory; Ab initio calculations; Structural disorder; Nanoparticle; Visible spectra; Deformation; Photoluminescence